Pengembangan Aplikasi Monitoring Keterlambatan Kehadiran Siswa SMK Muhammadiyah 1 Penajam Paser Utara Berbasis Web - Bima Satria; Abdul Rahim (BADAN PENERBIT STIEPARI PRESS, 2024)
The development of a student attendance delay monitoring application at SMK Muhammadiyah 1 Penajam Paser Utara is the main focus of this activity. By utilizing web-based technology using PHP and MySQL, the goal of this community service is to improve the efficiency of managing student attendance. The implementation process involves needs analysis, application design, development, testing, and training of school staff. Application installation, data collection, monitoring, and routine maintenance are practical steps taken. Community involvement focused on socializing the application to students and school security/gatekeepers. The evaluation of the activity included an assessment of success, positive impact and reflection on the application development process. Conclusions and recommendations from this activity form the basis for improvement and development of similar activities in the future.